Environmental project evaluation in developing countries: Valuing the environment as input - Edward B. Barbier (Fondazione Eni Enrico Mattei (FEEM), 1998)
An important evaluation problem in developing countries is assessing the value and optimal use of environmental resources as inputs into production. This is a key methodology required for many general evaluation approaches, e.g. ensuring the most efficient use of a resource requires incorporating environmental costs and benefits, and comparing the returns from competing uses. However, implementing this approach requires valuing the role of ecological services and resources in contributing to, supporting and protecting economic activity. To illustrate these issues, the paper draws on several case studies, such as allocating agricultural land among competing uses (e.g. gum arabic versus annual crops in Sudan), diversion of water from downstream floodplains for upstream water developments (e.g. Hadejia-Jama'are floodplain, Northern Nigeria), and evaluating the benefits of ecological services in support of economic activity in a dynamic context (e.g. mangrove-fishery linkages in Campeche, Mexico).
Keywords: O1; Q0; Q2; 330; Developing countries; Evaluation; Ecological services; Environmental input; Production function approach; Project appraisal; Valuation; Rohstoffpolitik; Entwicklungsprojekt; Projektbewertung; Allokationseffizienz; Natürliche Ressourcen; Produktionsfunktion; Theorie; Entwicklungsländer